Aplikasi Dua Paket Pupuk Majemuk pada Tanaman Tebu Ratoon yang Ditanam dengan Juring Tunggal dan Ganda - ,, lestari; Djumali, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Area of ratoon cane (RC) in Indonesia is more than 75% of total area of cane with productivity lower than plant cane (PC). To improve the productivity proper fertilizer application is required in accordance with the planting system used. This study was aimed to acquire a package of NPK compound fertilizer efficient for several planting systems of ratoon cane. The experiment was conducted in Muktiharjo Research Station, Pati in October 2013-September 2014. Two packages of compound fertilizer, i.e. 15N:15P:15K:10S formula package (500 kg compound fertilizer + 600 kg ZA ha-1) and 16N:8P:18K:2S:2Si formula package (500 kg compound fertilizer + 100 kg ZA ha-1) were arranged in randomized block design with four replications. Both packages were applied to two single row planting systems and two double row planting systems. The results showed that in single row planting system with both center - to - center (ctc) distances, i.e. 130 and 110 cm, the application of 16N:8P:18K:2S:2Si formula package resulted productivity, sugar content, and sugar yield that are no different from those with 15N:15P:15K:10S formula package. However, in double row planting systems with ctc 50/170 cm, 16N:8P:18K:2S:2Si formula package increased 9.20% sugar yield. The profit from 16N:8P:18K:2S:2Si formula package (12.07 million-14.23 million rupiah ha-1) in single row planting systems were lower than that of 15N:15P:15K:10S formula package (13.15 million-15.15 million rupiah ha-1). However in double row planting systems with ctc 50/170 cm, 16N:8P:18K:2S:2Si formula package produces profits (39.92 million rupiah ha-1) higher than with 15N:15P:15K:10S formula package (28.49 million rupiah ha-1).Keywords: planting-system, productivity, sugar-content, sugar-yield